Innovative teaching learning method-simulation based learning in community medicine - Bansod, Vaishali P.; Kulkarni, Shraddha S.; Khandre, Ruchita R. (International Journal Of Community Medicine And Public Health, 2023)
As per the new competency-based medical education curriculum, teaching and learning methods have been shifted from teacher-centric to student-centric to provide students with opportunities for diverse learning experiences through interactive learning. So, the department introduced innovative teaching in the classroom environment to make students understand the concept of community diagnosis in detail so that it will be beneficial for them while executing an actual visit to their family. A village was simulated in the classroom; students were randomly identified as medical students who were going to interact with villagers for the purpose of community diagnosis, whose roles were played by the remaining students. After that, the student explained the process with input from faculty. Feedback from students was taken through a Google form about the activity. There was a self-driven response from students with their active participation. They felt that it was a very interactive class and it prepared them for the field visit. Such simulation activities can be used as a teaching and learning method for relevant competencies with limited resources.